Effect of the ethanolic extract of red roselle calyx (Hibiscus sabdariffa L.) on hematocrit, platelets, and erythrocytes in healthy volunteers - Setianingsih, Siti; Nurani, Laela Hayu; Rohman, Abdul (Pharmaciana, 2018)
Roselle calyx (Hibiscus sabdariffa L) is widely used as an antioxidant, antihepatotoxic, diuretic, anti-cholesterol, and immunostimulant. Roselle contains anthocyanin and quercetin that have antioxidant activity. This study aimed to determine the effects of the ethanolic extract of roselle calyx on hematocrit, platelets, and erythrocytes in healthy volunteers during the 30-day administration and 15 days after it ceased. This study employed pre- and post-treatment design on 21 healthy volunteers, comprising 11 males and 10 females who fulfilled the inclusion criteria and filled out the informed consent form willingly. Volunteers were provided with roselle capsules for 30 days with a dosage of 500 mg a day taken 10-15 minutes after dinner. The hematologic examination was performed on Day 0, 31, and 45, including the measurement of hematocrit, platelet, and erythrocyte levels using a hematology analyzer. The obtained data were analyzed in SPSS with paired t-test and Wilcoxon test. The results showed that the hematocrit, platelets, and erythrocytes of all male and female volunteers on Day 0, 31, and 45 were within the normal range. The comparison analysis affirmed that there was no significant difference between these three parameters from Day 0 to 31, Day 31 to 45, and Day 0 to 45 (p>0.05). As a conclusion, the administration of the ethanolic extract of roselle calyx with a dosage of one 500mg capsule per day for 30 days did not affect the hematocrit, platelets, and erythrocytes in healthy volunteers. There was also no delayed effect on these three hematological parameters 15 days after the administration stopped.